THE GOND ARTS AND HANDICRAFTS SHOWCASE THE CULTURAL TRADITION OF THE GOND TRIBE IN KEONJHAR DISTRICT - Naik, Gourimani; Tripathy, Sishir Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Odisha’s tribal heritage is rich and diverseand among its many communities the Gond people of Keonjhar district stand out for their vibrant cultural traditions. This study focuses on the Gonds’ artistic expressionsespecially their paintings, crafts and traditional dancesthat continue to thrive in northern Odisha. The Gond community is particularly known for the intricate artwork they paint on the outer walls of their homes believing it brings good fortune.The research concentrates on Gond art found in the Telkoei and Ghatagaon blocks of Keonjhar examining the unique styles, patterns, motifs, colour choices and materials used. It also highlights the organizations working to preserve and promote this artistic heritage.The Gond people are equally known for their traditional dances including the Sword Dance. While these dances are still performed in Keonjhar and neighbouring Mayurbhanj the Sword Dance is now at risk of disappearing making preservation efforts urgent.The Gond tribe is one of the most significant tribal communities in Odisha and Central India. The name "Gond" is believed to derive from the word “Kond,” referring to the lush green hills described in their Dravidian language. The Gonds of Keonjhar are especially recognized for their folk art and cultural traditions painting, music and dance which offer valuable insights for scholars and cultural historians. This study represents a modest but meaningful effort to document and preserve these important aspects of Gond cultural life.